Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Which value of [tex]\( x \)[/tex] makes the two matrices inverses of each other?

[tex]\[
\left[\begin{array}{ll}
5 & 2 \\
2 & 1
\end{array}\right]
\left[\begin{array}{cc}
1 & -2 \\
x & 5
\end{array}\right]
\][/tex]


Sagot :

To determine the value of [tex]\( x \)[/tex] that makes the two matrices inverses of each other for the given matrices:
[tex]\[ A = \begin{bmatrix} 5 & 2 \\ 2 & 1 \end{bmatrix} \quad \text{and} \quad B = \begin{bmatrix} 1 & -2 \\ x & 5 \end{bmatrix}, \][/tex]
we need to find [tex]\( x \)[/tex] such that the product of the matrices [tex]\( A \)[/tex] and [tex]\( B \)[/tex] is the identity matrix [tex]\( I \)[/tex]:
[tex]\[ A \cdot B = I = \begin{bmatrix} 1 & 0 \\ 0 & 1 \end{bmatrix}. \][/tex]

Let's multiply the matrices [tex]\( A \)[/tex] and [tex]\( B \)[/tex].

[tex]\[ A \cdot B = \begin{bmatrix} 5 & 2 \\ 2 & 1 \end{bmatrix} \begin{bmatrix} 1 & -2 \\ x & 5 \end{bmatrix} \][/tex]

Perform the matrix multiplication:
[tex]\[ A \cdot B = \begin{bmatrix} (5 \cdot 1 + 2 \cdot x) & (5 \cdot -2 + 2 \cdot 5) \\ (2 \cdot 1 + 1 \cdot x) & (2 \cdot -2 + 1 \cdot 5) \end{bmatrix} = \begin{bmatrix} 5 + 2x & -10 + 10 \\ 2 + x & -4 + 5 \end{bmatrix} = \begin{bmatrix} 5 + 2x & 0 \\ 2 + x & 1 \end{bmatrix} \][/tex]

Now, we set the product equal to the identity matrix and solve for [tex]\( x \)[/tex]:

[tex]\[ \begin{bmatrix} 5 + 2x & 0 \\ 2 + x & 1 \end{bmatrix} = \begin{bmatrix} 1 & 0 \\ 0 & 1 \end{bmatrix} \][/tex]

From the matrix equality, we get the following system of equations:
[tex]\[ 5 + 2x = 1 \quad \text{(1)} \][/tex]
[tex]\[ 2 + x = 0 \quad \text{(2)} \][/tex]

First, solve equation (2) for [tex]\( x \)[/tex]:
[tex]\[ 2 + x = 0 \][/tex]
[tex]\[ x = -2 \][/tex]

Therefore, the value of [tex]\( x \)[/tex] that makes the two matrices inverses of each other is [tex]\( x = -2 \)[/tex].

To verify, substitute [tex]\( x = -2 \)[/tex] back into [tex]\( B \)[/tex] and check that [tex]\( A \cdot B = I \)[/tex]:
[tex]\[ B = \begin{bmatrix} 1 & -2 \\ -2 & 5 \end{bmatrix} \][/tex]
[tex]\[ A \cdot B = \begin{bmatrix} 5 & 2 \\ 2 & 1 \end{bmatrix} \begin{bmatrix} 1 & -2 \\ -2 & 5 \end{bmatrix} = \begin{bmatrix} 5 \cdot 1 + 2 \cdot (-2) & 5 \cdot -2 + 2 \cdot 5 \\ 2 \cdot 1 + 1 \cdot (-2) & 2 \cdot -2 + 1 \cdot 5 \end{bmatrix} = \begin{bmatrix} 5 - 4 & -10 + 10 \\ 2 - 2 & -4 + 5 \end{bmatrix} = \begin{bmatrix} 1 & 0 \\ 0 & 1 \end{bmatrix} = I \][/tex]

Thus, when [tex]\( x = -2 \)[/tex], the matrices [tex]\( A \)[/tex] and [tex]\( B \)[/tex] are indeed inverses of each other.
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.